Investigating Nurses\' Intention to Stay in Intensive Care Units and Associated Factors at Medical Training Centers of Mazandaran University of Medical Sciences, Sari, in 2023 - Mohammad Ali Heidari Gorji; Razieh Moalemian Gorji; Mahbobeh Yaghoubian; Abolfazl Hossein Nataj; Fereshteh Araghian Mojarad (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Understanding the factors influencing nurse retention and developing effective strategies to address the ongoing nursing shortage is crucial. Therefore, this study aimed to examine the intention to remain among critical care unit nurses and the factors associated with it in the medical education centers of Mazandaran University of Medical Sciences in 2023. Materials and methods: This descriptive-analytical study included 365 nurses from the intensive care units of the medical education centers at Mazandaran University of Medical Sciences. The inclusion criteria were a bachelor's degree or higher in nursing, no self-declared history of mental disorders, and at least one year of experience working in an intensive care unit. Data were collected using a demographic information checklist and a questionnaire on the determinants of nurses' intention to stay in the hospital, designed by M. Satoh et al. Statistical analysis was performed using SPSS version 24. Results: A total of 365 nurses with an average age of 34.97± 7.21 years participated in this study. Among the individual factors, age (OR=0.29), gender (OR=1.81), marital status (OR=6.88), and among the occupational factors of the workplace department (OR=7.17), the employment status (OR=2.19), interest and attachment to the nursing profession (OR=1.65) and also the workplace hospital (OR=3.43-6.43) were the most important factors affecting the retention rate of nurses working in the critical care unit. Conclusion: The findings indicated that among individual factors, age, gender, and marital status, and among occupational factors, the department and hospital of employment, employment status, and interest and attachment to the profession were the most important factors influencing the retention rate of nurses working in the intensive care unit.